Miniaturized rotating disc rheometer test for rapid screening of drag reducing marine coatings. (4th September 2015) - Dennington, Simon; Mekkhunthod, Ponkrit; Rides, Martin; Gibbs, David; Salta, Maria; Stoodley, Victoria; Wharton, Julian; Stoodley, Paul
Abstract: Frictional drag from the submerged hull surface of a ship is a major component of the resistance experienced when moving through water. Techniques for measuring frictional drag on test surfaces include towing tanks, flow tunnels and rotating discs. These large-scale methods present practical difficulties that hinder their widespread adoption and they are not conducive to rapid throughput. In this study a miniaturized benchtop rotating disc method is described that uses test discs 25 mm in diameter. A highly sensitive analytical rheometer is used to measure the torque acting on the discs rotating in water. Frictional resistance changes are estimated by comparing momentum coefficients. Model rough surfaces were prepared by attaching different grades of sandpaper to the disc surface. Discs with experimental antifouling coatings applied were exposed in the marine environment for the accumulation of microbial fouling, and the rotor was capable of detecting the increased drag due to biofilm formation. The drag due to biofilm was related to an equivalent sand roughness.